In-situ observation of low-power nano-synaptic response in graphene oxide using conductive atomic force microscopy - Hui,F; Liu,P; Hodge,S; Carey,T; Wen,C; Torrisi,F; Galhena,T; Tomarchio,F; Lin,Y; Moreno,E; Roldan,J; Koren,E; et al. (Small, 2021)
Multiple studies have reported the observation of electro-synaptic response in different metal/insulator/metal devices; however, most of them analysed large (>1 µm2) devices that do not meet the integration density required by the industry (1010 devices/mm2). Some studies employed a scanning tunnelling microscope (STM) to explore nano-synaptic response in different materials, but in this setup there is a nanogap between the insulator and one of the metallic electrodes (i.e. the STM tip), which is not present in real devices. Here we show how to use a conductive atomic force microscope (CAFM) to explore the presence and quality of nano-synaptic response in confined areas <500 nm2. For this study, we selected graphene oxide (GO) due to its easy fabrication and excellent electrical properties. Our experiments indicate that metal/GO/metal nano-synapses exhibit potentiation and paired pulse facilitation with low write current levels <1 µA (i.e. power consumption ~3 μW), controllable excitatory post-synaptic currents and long-term potentiation and depression. Our results provide a new method to explore nano-synaptic plasticity at the nanoscale, and point GO as an important candidate material for the fabrication of ultra-small (<500 nm2) electronic synapses fulfilling the integration density requirements of neuromorphic systems.